2013
DOI: 10.1111/zph.12064
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐Sectional Study Examining the Prevalence and Risk Factors for Anti‐Microbial‐Resistant Generic Escherichia coli in Domestic Dogs that Frequent Dog Parks in Three Cities in South‐Western Ontario, Canada

Abstract: Anti-microbial resistance can threaten health by limiting treatment options and increasing the risk of hospitalization and severity of infection. Companion animals can shed anti-microbial-resistant bacteria that may result in the exposure of other dogs and humans to anti-microbial-resistant genes. The prevalence of anti-microbial-resistant generic Escherichia coli in the faeces of dogs that visited dog parks in south-western Ontario was examined and risk factors for shedding anti-microbial-resistant generic E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The prevalence of resistant E . coli isolates in raccoon fecal (8%; 95% CI, 6–10) and soil samples (8%; 95% CI, 6–10) from conservation areas was slightly lower to what was found in pet dogs visiting dog parks in southwestern Ontario in 2009 (11%; 95% CI, 9–14; [50]). However, resistance to CIP or NAL was not detected in E .…”
Section: Discussionmentioning
confidence: 89%
“…The prevalence of resistant E . coli isolates in raccoon fecal (8%; 95% CI, 6–10) and soil samples (8%; 95% CI, 6–10) from conservation areas was slightly lower to what was found in pet dogs visiting dog parks in southwestern Ontario in 2009 (11%; 95% CI, 9–14; [50]). However, resistance to CIP or NAL was not detected in E .…”
Section: Discussionmentioning
confidence: 89%
“…Within the social sciences, investigations into the relationships between spatial and temporal patterns of dog-walking, dog-to-dog contact, and dog demographics have indirectly explored behaviours that could influence the risk of GI disease transmission in dogs [3,[11][12][13]. However, only a limited number of studies have investigated the extent to which parks might pose risks for infection and transmission of GI parasites in dogs [2,7,9,[13][14][15][16][17][18][19][20][21], a relevant query given that in urban settings, parks figure prominently as dog-walking destinations [22]. Giardia spp.…”
Section: Introductionmentioning
confidence: 99%
“…cysts have been isolated from undisposed dog faeces within parks [19,20]. Other parkrelated behaviours that may pose risks for infection and transmission of GI parasites, including Giardia spp., have been investigated, but with mixed results [2,7,9,[13][14][15][16][17][18]. In particular, Wang et al [18] reported that dogs taken to parks in an urban region of the United States had a higher risk of infection with Giardia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a steady increase in usage of antimicrobial agents for companion animals, in particular for dogs, has been observed in Europe over the last years (Ewers and others 2011). Previous studies carried in horses and dogs have determined several risk factors associated with the carriage of antimicrobial-resistant E. coli in the faeces, like recent hospitalisation and antimicrobial treatment in the previous 10 days (Maddox and ­others 2012, Procter and others 2013). …”
Section: Introductionmentioning
confidence: 99%